Clinical Klein!! Hinshelwood, R (1994) Clinical Klein. London: Free Association Books. ISBN 1-85343-315-2. - Ivey, Gavin (PINS-Psychology in Society, 2026)
Object relations theory is perhaps the dominant discourse in contemporary clinical psychoanalysis. Moreover, it seems to have won over many former critics of psychoanalysis, as evidenced by the extent to which object relations metaphors have penetrated psychotherapeutic approaches traditionally hostile to psychoanalysis. For example, concepts such as introjection and internalisation, containing, holding, good enough mothering, etc. have become common coin in circles who remain avowedly antagonistic to Freudian concepts and methods. The current clinical popularity of object relations theory arises from the selective appropriation of those authors and concepts which appear "cuddlier" than Freudian psychoanalysis, with its discomforting emphasis on oedipal sexuality and aggression. This is ironic as Melanie Klein, one of the originators of object relations theory, based her approach on an unflinching portrayal of humankind as driven by primitive unconscious oral and anal impulses deriving from the eternal opposition of life and death instincts. Simply stated, Klein’s object relations theory, which derived from her psychoanalytic treatment of young children and psychotic adults, is concerned with demonstrating how our earliest interactions with parental figures gives rise to primitive phantasies of orally incorporating these figures These introjected parental "objects" and our unconscious phantasied loving and destructive interaction with them constitutes the essence of our internal world, and profoundly influences our perceptions of the external world.